2012
DOI: 10.1007/s10529-012-0911-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of recombinant human cyclooxygenase 1 from stably-transfected Drosophila melanogaster S2 cells by dimethyl sulfoxide is mediated by up-regulation of nitric oxide synthase and transcription factor Kr-h1

Abstract: Recombinant human cyclooxygenase 1 (COX-1) was expressed from stably-transfected Drosophila melanogaster S2 (S2) cells. DMSO improved the expression of recombinant COX-1 by 180 %. DMSO increased the expression of nitric oxide synthase (NOS) at both the RNA and protein levels; NOS expression was closely correlated with the synthesis of recombinant COX-1 mRNA in stably-transfected S2 cells. DMSO also induced the gene encoding Kr-h1 which binds to the CACCC element of the metallothionein promoter to enhance the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Thus, DMSO increases the expression of recombinant COX-1 in S2 cells by upregulating NOS and the transcriptional factor Kr-h1. 22 No similar mechanisms through which DMSO increases recombinant gene expression in DF1 cells have been described.…”
Section: Purification and Bioactivity Assay Of The Fusion Proteinmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, DMSO increases the expression of recombinant COX-1 in S2 cells by upregulating NOS and the transcriptional factor Kr-h1. 22 No similar mechanisms through which DMSO increases recombinant gene expression in DF1 cells have been described.…”
Section: Purification and Bioactivity Assay Of The Fusion Proteinmentioning
confidence: 98%
“…19 Recently, a study reported that DMSO can increase the expression of recombinant cyclooxyenase 1 (COX-1) in stably transfected insect S2 cells. 22 DMSO increased the expression of nitric oxide synthase (NOS), which is closely related with the synthesis of recombinant COX-1 mRNA. DMSO also induced Kr-h1 gene expression and enhanced the synthesis of recombinant COX-1 proteins.…”
Section: Purification and Bioactivity Assay Of The Fusion Proteinmentioning
confidence: 99%
“…Stably transfected S2 cells expressing recombinant COX-1 were generated via co-transfection with pMT/BiP-His-COX-1 and pCoHygro [19]. Stably transfected S2 cells were grown at 27˚C in T-25 flasks in 3 mL of Shields and Sang M3 insect medium (Sigma-Aldrich, St. Louis, MO, USA) containing 10% insect medium supplementary (IMS, Sigma-Aldrich) and 300 μg/mL hygromycin B.…”
Section: Cell Culturementioning
confidence: 99%
“…DMSO is thought to have a broad impact on many aspects of gene expression in animal and insect cells [14][15][16]. DMSO enhanced the production of recombinant proteins such as rotavirus VP7, human cyclooxygenase 1 and 2 (COX-1 and 2) from stably transfected S2 cells [17][18][19]. Recently, we reported that DMSO increased synthesis of Drosophila NOS (dNOS) at both the RNA and protein levels, and that dNOS expression is closely related to synthesis of recombinant COX-1 mRNA in stably transfected S2 cells [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation